Postmodern Teachers’ Self-understanding in Sekolah Penggerak - Prasetyo, Aditya Pandu; Ratri, Devinta Puspita; Unsiah, Frida; Prasodjo, Pandu (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2025)
This study investigated how teachers enhanced their professional self-understanding as educators and how this self-understanding influenced their teaching performance. The study adopted a narrative inquiry research design. Qualitative data were collected through semi-structured interviews, guided by Kelchtermans’ theory. The data were gathered from seven teachers in Sekolah Penggerak, categorized into two groups: novice teachers and experienced teachers. Thematic data analysis was used to analyze the qualitative data. The research drew two main conclusions regarding teachers’ professional identities and the impact of continuous learning on their performance. First, most teachers unequivocally identify themselves as educators. Second, professional self-understanding significantly impacts teachers' teaching performance. The study suggested several recommendations for future research to expand upon its findings and provided more comprehensive insights into professional self-understanding in various educational contexts.